Some analysis on conjugacy search problem for Diffie-Hellman protocol - Jusoo, S. H.; Mohamad, Mohd Sham; Sulaiman, Sahimel Azwal; Faisal, . (Penerbit UMP, 2022)
The field in nonabelian group-based cryptosystem have gain attention of the researchers as it expected to offers higher security when confronted with quantum computational due to more complex algebraic structures. Hence, this paper intents to give an overview on Diffie-Hellman protocol considering the mathematically hard problem such as the conjugacy search problem in a group G. In this paper we provide examples for G of non abelian group particularly the group of SL(2,3).